2016
DOI: 10.1017/rep.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Causal Impact of the Voting Rights Act Language Minority Provisions

Abstract: The following study investigates the causal impact of the Voting Rights Act (VRA) language minority provisions, which mandate multilingual election assistance if certain population thresholds are met. While lower rates of Latino and Asian American political participation are often attributed to language barriers, scholars have yet to establish a direct impact of the provisions on electoral behavior. Building off of previous state-and county-level analyses, we leverage an individuallevel voter file database to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Printing of ballots in multiple languages, hiring poll workers fluent in other languages, and providing instructions, directions, and other election materials in multiple languages all add to the costs of election administration. Additionally, language assistance has been shown to increase voter turnout amongst Latinx and Asian American voters (Marschall and Rutherford, 2015;Fraga and Merseth, 2016). Consequently, language assistance could also have a mitigating effect on cost per voter because it may increase the number of voters participating who might not do so otherwise.…”
Section: Legal Requirements For Special Needs Populationsmentioning
confidence: 99%
“…Printing of ballots in multiple languages, hiring poll workers fluent in other languages, and providing instructions, directions, and other election materials in multiple languages all add to the costs of election administration. Additionally, language assistance has been shown to increase voter turnout amongst Latinx and Asian American voters (Marschall and Rutherford, 2015;Fraga and Merseth, 2016). Consequently, language assistance could also have a mitigating effect on cost per voter because it may increase the number of voters participating who might not do so otherwise.…”
Section: Legal Requirements For Special Needs Populationsmentioning
confidence: 99%
“…In his work, Ives emphasizes the importance of linguistic justice, or the fair distribution of language resources and opportunities. In addition, according to Fraga & Merseth (2016), lower rates of Latino and Asian American's political participation in the United States can be attributed to language barriers. As shown above, language barriers can cause a number of social inequalities.…”
Section: Potential Conflicts Of Multilingualismmentioning
confidence: 99%
“…Our survey of the literature showed that most posttreatment registrant studies adopt one of two strategies. Some studies, which are typically cross‐sectional, simply use the registration file as the universe of analysis and calculate turnout or partisanship rates as the proportion of voters or partisans among registrants (e.g., Barreto ; Barreto, Segura, and Woods ; Fraga and Merseth ; Hersh ; Hersh and Nall ). Other studies rely on voter files to calculate the numerator of interest (number of voters or partisans), but calculate turnout or partisanship rates using a measure of the potential electorate obtained from a secondary source as the denominator (Cepaluni and Hidalgo ; Fraga ; Meredith ).…”
mentioning
confidence: 99%